Experimental examination on the effectiveness of loss prevention technology: a case study. (15th December 2009) - Patrick, Ximena; Kovach, Jami; Cheng, Liang-Chieh (Victor)
The negative impact of inventory shrinkage on bottom line performance in the retail industry reaches billions of dollars each year. Previous recommendations suggest that inventory shrinkage is a function of the merchandise tagging strategy. The current technology available for securing merchandise includes both electronic article surveillance (EAS) and radio frequency identification (RFID) systems. However, few studies have empirically examined the impact of tagging strategies on inventory management. The present study attempts to fill this gap in the literature by experimentally investigating the relationship between merchandise tagging and inventory control. Our work includes a field experiment to test the effect of EAS systems on inventory shrinkage in a retail setting. Our findings indicate that merchandise tagging systems exhibit strong capabilities in terms of reducing inventory shrinkage and enhancing retail profitability. These conclusions provide evidence in favour of the logistical and financial benefits of this technology with respect to shrinkage reduction.